PENGENALAN KOSAKATA BAHASA INGGRIS “THINGS AROUND US” PADA ANAK SANTRI PANTI ASUHAN AISYIYAH LUWUK - Nurhaida Lakuana; Yusniati N. Sabata (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2024)
English education as an international language is an important aspect in improving the quality of human resources, especially for children in orphanages who often have limited access to education in this language. The English vocabulary introduction program with the theme "Things Around Us" was implemented at the Aisyiyah Luwuk Orphanage with the aim of improving the students' mastery of English vocabulary. Through interactive and contextual methods such as word games, songs and drawing activities, this program succeeded in increasing the average score on written tests from 45% to 80% and oral tests from 50% to 85%. Observations and interviews showed increased children's participation, motivation and confidence in using new vocabulary. This program not only provides academic benefits but also has a positive impact on children's personal development. With this success, it is hoped that similar programs can be implemented in more orphanages to provide the same benefits, opening up more opportunities in the future for less fortunate children.